COMMUNISM AND ITS INFLUENCE ON THE EMERGENCE OF ATHEISM - Ahmad Mukri Aji, Nur Rohim Yunus, Gilang Rizki Aji Putra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Karl Marx’s conception of communism is an anti-class society. There is no boundary between the peasants and the peasantry toward the feudalists and the bourgeoisie. This teaching aims to awaken the poor from the tyranny of the bourgeoisie, which dominates the economy of the world. The research approach used for this research is qualitative. The data used was extracted from a variety of scientific journal sources in the literature. The outcome of the research reveals that communism is not important to be enforced in today’s modern age, because of the human need to be free from state barriers and constraints. In addition to the notion of communism, it has an impact on the life of anti-religious or anti-God teachings (Atheism) since Karl Marx’s teachings call on communist people to abandon religion as an obstacle to the awakening of the broader population.